Comparisons of Cognitive Stimulation Therapy Between Community Versus Hospital-Based Settings: A Multi-Site Study. (February 2023) - Zubatsky, Max; Khoo, Yit Mui; Lundy, Janice; Blessing, Debra; Berg-Weger, Marla; Hayden, Deborah; Morley, John E.
Background: Non-pharmacological interventions such as Cognitive Stimulation Therapy (CST) have been shown to help persons living with dementia in improving cognitive function and recall. While previous CST interventions have been conducted largely with community populations, none have explored the outcomes of CST in larger healthcare settings. Our study explored differences of cognitive function, mood, and quality-of-life from CST groups both community and residential-based groups. Method: Participants ( N = 258) from academic and rural, hospital-based settings in Missouri engaged in 14-session psychosocial groups to aid reminiscence for enhanced cognitive function and recall. Results: Post-intervention cognitive function improvements occurred for community (t = −7.48, p < .001) and residential samples (t = −2.46, p < .05). Community groups showed significant improvement in overall mood related to their dementia (t = 6.37, p < .001). Conclusion: Healthcare providers should consider CST as a supplemental intervention for older patients receiving usual care for dementia-related symptoms.